The Integrative Function of Silent Synapses on Subplate Neurons in Cortical Development and Dysfunction - Kanold, Patrick O.; Deng, Rongkang; Meng, Xiangying (Frontiers in Neuroanatomy, 2019)
The thalamocortical circuit is of central importance in relaying information to the cortex. In development, subplate neurons (SPNs) form an integral part of the thalamocortical pathway. These early born cortical neurons are the first neurons to receive thalamic inputs and excite neurons in the cortical plate. This feed-forward circuit topology of SPNs supports the role of SPNs in shaping the formation and plasticity of thalamocortical connections. Recently it has been shown that SPNs also receive inputs from the developing cortical plate and project to the thalamus. The cortical inputs to SPNs in early ages are mediated by N-methyl-D-aspartate (NMDA)-receptor only containing synapses while at later ages α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-receptors are present. Thus, SPNs perform a changing integrative function over development. NMDA-receptor only synapses are crucially influenced by the resting potential and thus insults to the developing brain that causes depolarizations, e.g., hypoxia, can influence the integrative function of SPNs. Since such insults in humans cause symptoms of neurodevelopmental disorders, NMDA-receptor only synapses on SPNs might provide a crucial link between early injuries and later circuit dysfunction. We thus here review subplate associated circuits, their changing functions, and discuss possible roles in development and disease.